Positive Impacts of Olive Oil Enriched with Lycopene on the Plasma Antioxidant and Anti-Inflammatory Status of Hypercholesterolemic Patients - Meryem El Ouardi; Guillem Garcia-Llorens; Victoria Valls-Belles (Disease and Health: Research Developments Vol. 10, 2025)
Atherosclerosis is a chronic inflammatory disease that is responsible for several cardiovascular events such as ischemic heart disease, coronary artery disease, peripheral artery disease, and ischemic stroke. Olive oil and lycopene are foods that have potent antioxidant activity. The objective was to determine the effects of consumption of olive oil enriched with lycopene on oxidative stress biomarkers in hypercholesterolemic subjects. The study product sample “lycopene-olive oil” consisted of virgin olive oil enriched with lycopene (350 mg/L). Patients (n = 80) were recruited from the town of Moralzarzal, Madrid, Spain, including healthy men and women with cholesterol levels over 220 mg/dL. The effects of oil enriched with lycopene extract daily intake were examined for 1 month on plasma antioxidant capacity, lipid profile (triacylglycerols, total cholesterol, HDL-C; LDL-C, ox-LDL), biomarkers of oxidative stress, and inflammatory markers related to atherosclerosis risk (C-reactive protein (CRP), IL-6; sDC4L) in subjects with hypercholesterolemia (cholesterol > 220 mg/dL). In the group consuming olive oil-lycopene, significant increases (p < 0.05) in the levels of plasma lycopene concentration (0.146 ± 0.03 versus 0.202 ± 0.04 (\(μ\)mol/L)), \(α\)-carotene (0.166 ± 0.064 versus 0.238 ± 0.07) and \(β\)-carotene (0.493 ± 0.187 versus 0.713 ± 0.221) were observed. These results are linked with the increases of plasma antioxidants and decrease in biomarkers of oxidative stress (carbonyl groups, malondialdehyde and 8-hydroxy-deoxyguanosine) observed in the hypercholesterolemic group. In relation to the lipid profile, a significant decrease was observed in the levels of ox-LDL (781 ± 302 versus 494 ± 200), remaining unchanged in the levels of TG, cholesterol, HDL and LDL-C. Regarding inflammatory biomarkers, the levels of CRP and IL-6 decreased significantly. The positive results obtained in this study support the use of olive oil enriched with lycopene to reduce the risk of coronary disease. The results also indicate that triglyceride, cholesterol, LDL, and HDL levels did not change significantly. However, ox-LDL levels decreased significantly only in the group supplemented with lycopene-olive oil. In conclusion, this study suggests that foods containing olive oil and lycopene can significantly contribute to reducing LDL-induced oxidative stress.